Investigating differences in dietary patterns among a small cross-sectional study of young and old Pacific peoples in NZ using exploratory factor analysis: a feasibility study. Issue 3 (1st March 2019) - Tupai-Firestone, Ridvan; Cheng, Soo; Kaholokula, Joseph; Borman, Barry; Ellison-Loschmann, Lis
Abstract : Objectives: Obesity among Pasifika people living in New Zealand is a serious health problem with prevalence rates more than twice those of the general population (67% vs 33%, respectively). Due to the high risk of developing obesity for this population, we investigated diet quality of Pacific youth and their parents and grandparents. Therefore, we examined the dietary diversity of 30 youth and their parents and grandparents (n=34) to identify whether there are generational differences in dietary patterns and investigate the relationship between acculturation and dietary patterns. Methods: The study design of the overarching study was cross-sectional. Face-to-face interviews were conducted with Pasifika youth, parents and grandparents to investigate dietary diversity, that included both nutritious and discretionary food items and food groups over a 7 day period. Study setting was located in 2 large urban cities, New Zealand. Exploratory factor analyses were used to calculate food scores (means) from individual food items based on proportions consumed over the week, and weights were applied to calculate a standardised food score. The relationship between the level of acculturation and deprivation with dietary patterns was also assessed. Results: Three distinctive dietary patterns across all participants were identified from our analyses. Healthy diet, processed diet and mixed diet. Mean food scores indicated statistically significant differences between the dietary patterns for older and younger generations. Older generations showed greater diversity in food items consumed, as well as eating primarily a 'healthy diet'. The younger generation was more likely to consume a 'processed diet'. There was significant association between acculturation and deprivation with the distinctive dietary patterns. Conclusion: Our investigation highlighted generational differences in consuming a limited range of food items. Identified dietary components may, in part, be explained by specific acculturation modes (assimilation and marginalised) and high socioeconomic deprivation among this particular study population.